Global Prevalence of Periodontal Disease and Lack of Its Surveillance. (28th May 2020) - Nazir, Muhammad; Al-Ansari, Asim; Al-Khalifa, Khalifa; Alhareky, Muhanad; Gaffar, Balgis; Almas, Khalid
Abstract : Background . Periodontal disease is a public health problem and is strongly associated with systemic diseases; however, its worldwide distribution is not fully understood. Objective . To evaluate global data of periodontal disease: (1) among adolescents, adults, and older population and (2) in low-, middle-, and high-income countries. Methods . This ecological study included data of periodontal disease from the World Health Organization's data bank which are based on the Community Periodontal Index of Treatment Needs (CPITN code: 0 = no disease; 1 = bleeding on probing; 2 = calculus; 3 = periodontal pocket (PD) 4-5 mm; 4 = PD (6+ mm). Age- and income-related periodontal disease inequalities were evaluated across the globe. Results . Compared with 9.3% of adults and 9.7% of older persons, 21.2% of adolescents had no periodontal disease (P = 0.005 ). Nearly 18.8% of adolescents compared with 8.9% of adults and 5% of older persons had bleeding on probing (P ≤ 0.001 ). Similarly, 50.3% of adolescents, 44.6% of adults, and 31.9% older persons demonstrated the occurrence of calculus (P = 0.01 ). On the other hand, older persons had the highest prevalence of PD 4-5 mm and PD 6+ mm than adults and adolescents (P ≤ 0.001 ). The distribution of periodontitis (CPITN code 3 + 4) in adults differed significantly in low- (28.7%), lower-middle- (10%), upper-middle- (42.5%), and high-income countries (43.7%) (P = 0.04 ). However, no significant differences in periodontitis (CPITN code 3 + 4) were observed in adolescents and older persons in low- to high-income countries. Conclusions . Within the limitations of data, this study found that the distribution of periodontal disease increases with age. Periodontitis was the most common in older persons and in population from high-income countries.